ORGANIZATIONAL EXPERTISE AND DECISION MAKING IN CORPORATE AND COMPLEX ORGANIZATIONS - Amodio, Stefano (Annals of Spiru Haret University. Economic Series, 2022)
Abstract The ability to carry out coordination tasks within the group is identified with the leading role of the group itself. If this ability manifests itself continuously, it is an indispensable premise for the attribution of leadership to the one who demonstrates and exercises it. Leadership is therefore a quality, a gift that is not only a factor of appreciation for the individual, but also a valuable resource for the group. It usually happens that one or more members of an organization find it important to engage in seeking some influence on other members; this means making attempts to exercise authority. If these attempts are successful and are repeated over time, they can actually confer leadership on the one who has been the protagonist. in whatever sector they operate, companies need to reap the benefits offered by leaders capable of generating the emotional resonance in the company that allows everyone to realize their aspirations and make their potentials concrete. It is important to note that, while it may be easy to achieve individual and private emotional satisfaction, the task is more complex when a leader wants to create an emotional resonance in the group of his collaborators. The awareness of one’s individual emotional realities represents, for the entire organization of the company, the beginning of a useful analysis of the common habits on which those emotional realities are based and from which they are fed. In fact, this is precisely the starting point of the leader who wants to spread emotional intelligence in his organization